Bidirectional Effects Between Parental Care and Depression Among Adolescent Boys: Results From the Chinese Family Panel Studies - Wang, Jingyu; Jiao, Jian (Frontiers in Psychology, 2022)
Background: Research has consistently shown the adverse effects of inappropriate parenting on adolescent depression. Meanwhile, interpersonal theories of depression suggest that depressed individuals elicit frustration and rejection from their relational partners. Methods: Using two-wave data from the Chinese Family Panel Studies (CFPS), the present study examined the prospective relationships between parental care and adolescent depression. Participant were 426 adolescents (54.9% males) born in 1999 (ages at T1 and T2 were 11 and 13). Results: Results from the structural equation model showed that parental care prospectively and negatively predicted depression among both adolescent boys and girls. Inversely, adolescent boys’ depression, but not girls’ depression, negatively predicted subsequent parental care. Conclusion: The results suggest the interactive dynamic between parental care and adolescent depression as well as parents’ gendered responses to adolescent depression.